On a new subclass of univalent harmonic functions that defined by integral operator - Atshan, Wajas Ghalib; Hasan, Fatimah Haydar (Journal of Kufa for Mathematics and Computer, 2017)
In this paper, we investigate several properties of the harmonic class RLH(α,β,γ), we discuss the coefficient inequality, the distortion bounds theorem, the closure theorem, convex combinations, Bernardi integral operator and integral convolution property.